A New Measurement of 11Be(p, d) Transfer Reaction*Supported by the National Key Research and Development Program of China under Grant No 2018YFA0404403, and the National Natural Science Foundation of China under Grant Nos 11775004 and 11775036. (August 2018) - Jiang 蒋, Ying 颖; Lou 楼, Jian-Ling 建玲; Ye 叶, Yan-Lin 沿林; Pang 庞, Dan-Yang 丹阳; Chen 陈, Jie 洁; Li 李, Zhi-Huan 智焕; Ge 葛, Yu-Cheng 愉成; Li 李, Qi-Te 奇特; Li 李, Jing 晶; Jiang 蒋, Wei 伟; Sun 孙, Ye-Lei 叶磊; Zang 臧, Hong-Liang 洪亮; et al.
Abstract : A new 11 Be(p, d) transfer reaction experiment is performed in inverse kinematics with a radioactive 11 Be beam at 26.9A MeV. Three low-lying states, namely the 0 + ground state, the 2 + state at Ex = 3.37 MeV, and the multiplet at around 6 MeV in 10 Be, are populated by this one-neutron transfer reaction. These three states in 10 Be are clearly discriminated from the Q -value spectrum, which is rebuilt from energies and angles of the recoil deuterons in coincidence with 10 Be. A spectroscopic factor for each state is extracted by comparing the experimental differential cross sections to the theoretical calculation results using the finite range adiabatic distorted wave approximation method with different global nucleon-nucleus potentials. It is found that the newly extracted spectroscopic factors for the 0 + and 2 + states are consistent with the previous ones, but the factor for the multiplet is smaller than the value in the reference, and the possible reason is discussed.